2015
DOI: 10.1002/jaba.221
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral treatment of rumination: Research and clinical applications

Abstract: This brief review describes research on rumination treatment that emphasizes functional analysis, recent intervention methods (supplemental feeding, fixed-time stimulus presentation, continuous access to preferred stimulation), clinical implications, and procedural recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…Given that rumination persisted across consecutive alone sessions during which there were no programmed consequences, the results of the FAS suggested that Mike's rumination was likely maintained by automatic reinforcement. This is consistent with previous research in which functional analyses of rumination indicated that rumination is often maintained by automatic reinforcement (Luiselli, ). The middle panel of Figure shows results for the SAA.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Given that rumination persisted across consecutive alone sessions during which there were no programmed consequences, the results of the FAS suggested that Mike's rumination was likely maintained by automatic reinforcement. This is consistent with previous research in which functional analyses of rumination indicated that rumination is often maintained by automatic reinforcement (Luiselli, ). The middle panel of Figure shows results for the SAA.…”
Section: Resultssupporting
confidence: 93%
“…More recently, researchers, particularly those who conduct pre‐treatment functional analyses, have shifted toward more function‐based treatments. Because rumination is often maintained by automatic reinforcement (Luiselli, ), function‐based treatments in this context often involve antecedent manipulations aimed at either (a) arranging an abolishing operation for the occurrence of rumination or (b) establishing an appropriate, alternative response that produces similar oral stimulation. As such, in a recent review of behavioral interventions of rumination, Lang et al () reported that the most common intervention for chronic rumination involved diet manipulation (e.g., noncontingent access to food or liquid; Kliebert & Tiger, ) followed by competing oral stimulation (e.g., access to chewing gum; Rhine & Tarbox, ).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Behavioural therapy with post-prandial diaphragmatic breathing which reverses the oesophago-gastric pressure gradient is the mainstay of treatment and more efficacious than pharmacological therapy (Absah et al, 2016;Papadopoulos and Mimidis, 2007). Management options for rumination in patients with autistic spectrum disorder also include supplemental feedings to break the regurgitation cycle, utilisation of preferred stimuli as well as a focus on increased or alternative stimulation (Luiselli, 2015).…”
Section: Discussionmentioning
confidence: 99%